(untitled) (CAHIERS MAGELLANES-NS, 2024)
This systematic review explores the effectiveness of Collaborative Learning in enhancing Social Skills among Secondary School Students. Collaborative Learning, a pedagogical approach where students engage in group-based tasks, is grounded in critical theoretical frameworks, including Vygotsky’s Sociocultural Theory, Social Interdependence Theory by Johnson and Johnson, and Kolb’s Experiential Learning Theory. These theories highlight the role of social interaction in cognitive and emotional development, which aligns with the collaborative model’s emphasis on peer engagement. Social skills like communication, empathy, teamwork, and conflict resolution are crucial for academic success, emotional well-being, and future employability. This review synthesizes findings from various studies that underscore the positive impact of collaborative learning methods-such as Think-Pair-Share, Jigsaw, Peer Tutoring, and Role-Playing-on students’ social skill development. Empirical evidence indicates Collaborative Learning fosters inclusivity, enhances interpersonal relationships, and improves communication and cooperation. Challenges such as free-riding and personality clashes are acknowledged, with recommendations for teacher guidance to maximize collaborative effectiveness. The review demonstrates that Collaborative Learning significantly improves social and academic outcomes, preparing students for future civic and professional roles.